Effects of Different Drying Methods on the Quality of Squid Cubes - Chen, H.; Zhang, M.; Fang, Zhongxiang; Wang, Y. (Taylor & Francis, 2013)
The effects of three different drying methods (e.g., intermediate infrared-assisted convection drying, low-frequency (915 MHz) microwave drying, and hot-air drying) on the quality of squid cubes were investigated. The quality parameters used to evaluate the drying efficiency were color, shrinkage, rehydration ratio, and hardness of the final dried products. The results showed that intermediateinfrared-assisted convection drying and low-frequency microwave drying have the advantages over hot-air drying in terms of drying rate, shrinkage percentage, and rehydration ratio. Low-frequency microwave-dried samples displayed a puffed structure and their hardness was the highest. The intermediate-wave infrared-assisted convection drying, at 60C, was identified as the best method for squid-cube drying in this study.